Confined microemulsion sono-polymerization of poly(ethylene glycol) nanoparticles for targeted delivery. Issue 56 (22nd June 2022) - Gao, Zhiliang; Li, Xiaoyu; Zhao, Kaijie; Geng, Huimin; Zhang, Peiyu; Ju, Yi; Huda, Pie; Howard, Christopher B.; Thurecht, Kristofer J.; Ashokkumar, Muthupandian; Hao, Jingcheng; Cui, Jiwei
Abstract : Confined sono-polymerization is developed to prepare poly(ethylene glycol) nanoparticles within water-in-oil microemulsions for targeted delivery. Abstract : Confined sono-polymerization is developed to prepare poly(ethylene glycol) nanoparticles within water-in-oil microemulsion, followed by post-functionalization with a bispecific antibody (anti HER2 and anti PEG) for targeted delivery of photosensitizers ( i.e., indocyanine green). The nanoparticles could specifically target to breast cancer cells ( i.e., SKBR3) that overexpress HER2 receptors for the inhibition of cancer cell growth under 808 nm laser irradiation. This study highlights a facile and controllable method to fabricate therapeutic nanoparticles capable of targeted delivery.